Abiotic Typology of the Rivers and Lakes of the Ukrainian Section of the Vistula River Basin and its Comparison with Results of Polish Investigations - Khilchevskyi, Valentyn K.; Grebin, Vasyl V.; Zabokrytska, Myroslava R. (BegellHouse, USA, 2019)
The typology of rivers and lakes of the West Bug and San transboundary river subbasins (the Vistula River basin) was carried out. The researches were based on provisions of the EU Water Framework Directive for the surface waters typology according to the system A, implemented in Ukraine and Poland.
Keywords: the West Bug River; EU Water Framework Directive; abiotic types; river; lake